Asian Involvement in Africa: A Perspective on Emerging Binaries in the Global South. (March 2014) - S, Shaji
The refashioned economies and polities of countries, notably in the Global South after the end of the Cold War, drastically altered the perceptions on binaries of conventional types at the international level—South/North, East/West, core/periphery and so on. Asian powers, such as, India and China, under the rapidly expanding processes of globalisation began to intensively involve in the developing world, notably in Africa, which was hitherto overlooked, in search of oil and natural resources, along with accessing their fledging markets. The criticisms generated on the Asian involvement in Africa, notably on the part of African scholars/observers, prompt us to revisit some of the established conceptions on North–South, South/South relations, critiquing the very essence of the 'Global South' in the contemporary period. In addition, economic ties/practices between Asian powers (such as, India and China) and African states, while blurring the old binaries, have the potential to create new binaries in the near future.